Study of Governing Mechanisms on Failure Properties of Filled Rubber Compound in Different Sulfur Crosslink Densities and Types - Atashi, H.; Shiva, M. (Asian Journal of Chemistry, 2010)
The effect of crosslink density changes on failure properties of SBR and NR/BR based compounds, tear behaviour, crack growth, tensile and abrasion, are investigated. The governing mechanisms on each behaviour are discussed. It is concluded that in lower crosslink densities, the presence of stronger bonds has a dominant role on failure behaviour and an increase of crosslinking specially within monosulfidic bonds is useful, so efficient curing system delivers better properties than conventional ones. However at moderate and high crosslinks, the failure properties diminish significantly because of governing of chain movement ability mechanism. In this situation no significant change has been observed between efficient and conventional curing systems. At very high corsslinks, where chain movement ability mechanism is governed, the longer polysulfidic crosslinks with dissipating capability of breakdown and reforming deliver better dematia crack growth. The same behaviour observed in NR based compounds but the differences were diminished with induced-crystallinity capability of NR rubber and super abrasion behaviour of BR rubber.